Disentangling elevational and vegetational effects on ant diversity patterns - Lasmar, Chaim J.; Ribas, Carla R.; Louzada, Julio; Queiroz, Antônio C.M.; Feitosa, Rodrigo M.; Imata, Mayara M.G.; Alves, Guilherme P.; Nascimento, Gabriela B.; Neves, Frederico S.; Domingos, Daniel Q. (Acta oecologica (Montrouge), 2020)
When aiming to assess the effects of elevation on animal diversity, many studies have been carried out in different vegetation types occurring across elevational gradients. Thus, it remains unclear if any changes observed in species richness are caused by factors directly associated with elevation or are caused by vegetation change across the gradient. Here, we disentangled the effects of elevation from changes in vegetation by assessing ant diversity patterns along an elevational gradient. We analyzed patterns of ant diversity utilizing two different sampling approaches across the elevational gradient: (1) a standardized sampling including only forest formations and (2) a non–standardized sampling including forest (low elevational bands) and grasslands (high elevational bands). We sampled ants at eight elevational bands of Atlantic Forest in Brazil, and the highest three bands were sampled at both forest and grassland habitat. We found that the two approaches produce contrasting patterns of alpha and beta diversity, but the same pattern of gamma diversity. However, in the non–standardized sampling approach, the regression analysis produced a reduced explanation of the species richness gradient and a decrease in the elevational effect size. Different patterns found in the two approaches could be due to distinct environmental conditions in these habitats. In conclusion, our results highlight the potential bias of non–standardizing vegetation type across elevational gradients when assessing elevational patterns of species diversity. •We disentangled elevational and vegetational effects on ant diversity patterns utilizing different approaches.•(1) a standardized sampling within one vegetation type and (2) a non-standardized sampling including two vegetation types.•Effects of elevational gradient on α-diversity and β-diversity clearly differed between the two approaches.•For ɣ–diversity, sampling in the same vegetation type gradient leads to stronger resulting.•Sampling in different vegetation types across an elevational gradient produces distinct diversity patterns.